Sistem Pendukung Keputusan Penilaian Kinerja Pegawai Universitas Katolik Santo Thomas Medan menggunakan Metode TOPSIS - Harianja, Andy Paul; Sinaga, Andri Mahdalena (KAKIFIKOM : Kumpulan Artikel Karya Ilmiah Fakultas Ilmu Komputer, 2024)
Education personnel are personnel in charge of planning and carrying out administration, management, development, and technical services to support the educational process in educational units. Santo Thomas Catholic University is currently located at Jl. Setia Budi No.479-F Tanjung Sari Medan. Santo Thomas Catholic University is under the auspices of the Archdiocese of Medan (KAM). In general, a decision support system is a system that is capable and provides problem solving capabilities with semi-structured and unstructured conditions. Processing in the current assessment process which still uses conventional or manual methods using paper and then divided per unit to be filled in so that the process becomes long or prone to errors and errors and in the process of assessing employee performance there is often a delay in assessing promotion. TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) is used as one of the methods in processing data for each alternative in the database, where in the end the processing is in the form of ranking based on criteria that have been determined.is in the form of determining rankings based on predetermined criteria.